Cloning of the glutamine synthetase gene from group B streptococci. - Suvorov, A N (1997)
The glnA gene from the human pathogen Streptococcus agalactiae was cloned from a genomic library prepared with the lambda phage vector lambdaDASHII. A 4.6-kb DNA fragment of one of the recombinant phages was subcloned in pUC18. This Escherichia coli clone expressed a 52-kDa protein encoded by a 1,341-bp open reading frame. The nucleotide sequence of the open reading frame and the deduced amino acid sequence shared a significant degree of homology with the sequences of other glutamine synthetases (GS). The highest homology was between our deduced protein and GS of gram-positive bacteria such as Bacillus subtilis, Bacillus cereus, and Staphylococcus aureus. Plasmids with the cloned streptococcal glnA were able to complement E. coli glnA mutants grown on minimal media. Rabbit antisera to streptococcal GS recombinant protein recognized not only the recombinant protein but also a similar-sized band in mutanolysin extracts of all group B streptococcal strains tested, regardless of polysaccharide type or surface protein profile. The amino acid sequence of the deduced protein had similarities to other streptococcal cell-surface-bound proteins. The possible functional role of the immunological features of streptococcal GS is discussed.